Sustainable Energy Systems and Green Hotel Practices in Hotels in Tamale Metropolis, Ghana - APPIAH, Patricia Animah; ADONGO, Raymond; SAFO, Abdul-Rafiw (Journal of Environmental Management and Tourism; Vol 14 No 7 (2023): JEMT, Volume XIV, Issue 7(71), Winter 2023DO - 10.14505/jemt.v14.7(71).09, 2023)
The hotel sector, along with numerous other tourism-related industries, significantly poses a threat to the environment through its extensive consumption of resources like water, energy, and non-durable items. The hotel industry is also well known for its large-scale discharge of raw and solid waste in varying proportions. As a result, numerous hotels have begun implementing innovative approaches to enhance the sustainability of their operations in efforts to alleviate their environmental impact while also addressing the increasing environmental concerns expressed by customers. Employing a cross-sectional design and quantitative approach and using both descriptive and inferential analysis, we assess sustainable energy systems and green hotel practices in the Tamale metropolis, Ghana. We find that majority of hotels in the Tamale metropolis have written green management policy. We also find that cost and customers understanding of green policies are the main challenges hindering their adaptation and implementation of sustainable energy systems. The study establishes a significant relationship between level of education and use of green energy practices. Again, the study finds staff strength to be highly inter-linked with the existence of green management policy. To this end, we recommend that operators should implement training programs for staff, replace fossil fuels with renewable energy sources and educating the citizens to foster increased awareness and trust in renewable energy systems, as well as to provide proper training for their effective utilization .